2020
DOI: 10.1111/hiv.12937
|View full text |Cite
|
Sign up to set email alerts
|

Excess liver‐related mortality among people with AIDS compared to the general population: an Italian nationwide cohort study using multiple causes of death

Abstract: Liver diseases have become a leading cause of death among people with AIDS (PWA). This study aimed to investigate whether PWA experienced excess mortality related to liver diseases as compared to the general population (non-PWA), using a multiple cause of death (MCoD; i.e. all conditions reported on death certificates) approach. Methods A population-based, nationwide, retrospective cohort study was conducted among Italian people, aged 15-74 years, who had been diagnosed with AIDS since 2006. Date of death and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Several recent studies found that PLHIV have relatively poorer prognosis and survival for some NADCs in comparison with the general population. 54 , 55 , 56 , 57 , 58 For example, studies conducted in the US reported elevated standardized mortality ratios (SMRs) for some common NADCs, such as cancers of the liver, lung, and colon and rectum in PLHIV. 56 , 57 , 58 Understanding the risk of death attributable to various NADCs could inform disease management and treatment among PLHIV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies found that PLHIV have relatively poorer prognosis and survival for some NADCs in comparison with the general population. 54 , 55 , 56 , 57 , 58 For example, studies conducted in the US reported elevated standardized mortality ratios (SMRs) for some common NADCs, such as cancers of the liver, lung, and colon and rectum in PLHIV. 56 , 57 , 58 Understanding the risk of death attributable to various NADCs could inform disease management and treatment among PLHIV.…”
Section: Introductionmentioning
confidence: 99%
“… 54 , 55 , 56 , 57 , 58 For example, studies conducted in the US reported elevated standardized mortality ratios (SMRs) for some common NADCs, such as cancers of the liver, lung, and colon and rectum in PLHIV. 56 , 57 , 58 Understanding the risk of death attributable to various NADCs could inform disease management and treatment among PLHIV. To the best of our knowledge, however, so far there has been a lack of summary and meta-analysed data on the mortality risk of NADCs among PLHIV.…”
Section: Introductionmentioning
confidence: 99%
“…Although we used PSM to control for selection bias, a retrospective cohort study is intrinsically biased. Furthermore, specific important variables associated with mortality, such as adherence to ART, body mass index, anemia, hyperlipemia, and liver injury [ 31 33 ], were not recorded when patients switched to second-line ART.…”
Section: Discussionmentioning
confidence: 99%
“…AST/ALT≥50 u/L, which was de ned as Liver injury [26], was the risk factor of death of HIV/AIDS patients. Liver injury would induce cirrhosis and hepatocellular carcinoma and increase the HR of death in HIV/AIDS patients [27,28].…”
Section: Discussionmentioning
confidence: 99%